Randomized controlled trial evaluating participation and yield of colonoscopy versus CT colonography screening. (March 2012) - Pickhardt, Perry J
Evaluation of: Stoop EM, de Haan MC, de Wijkerslooth TR et al. Participation and yield of colonoscopy versus non-cathartic CT colonography in population-based screening for colorectal cancer: a randomized controlled trial. Lancet Oncol. 13(1), 55–64 (2011). Colorectal cancer is a common yet preventable condition. Population screening attempts suffer from a lack of widespread participation with the currently available options. Computerized tomography colonography (CTC) represents a promising addition to the screening armamentarium. CTC is less invasive than optical colonoscopy but has been shown to be equivalent to colonoscopy for the detection of advanced neoplasia, which represents the primary target of screening and prevention. Although CTC has generally been preferred over colonoscopy by patients in most published studies, little hard evidence exists regarding the level of increase in screening participation related to CTC. The landmark trial under discussion adds key data in terms of participation rates for CTC screening relative to colonoscopy screening.